Infant´s growth and development assessment in the presence of congenital cardiopathies - a descriptive study - Ana Llonch Sabates; Erika Tatiana Marcondes David (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
First considerations: in spite of technological progresse in diagnosis, treatment and surgical techniques, which allowed today a larger survival and better life for children bearer of congenital cardiopatias, the growth and development deficits continues being one of the most common problems in those children. Objective: to assess the growth and development of children in the presence of congenital cardiopathie. Methods: this is an exploratory, descriptive, and field study using a quantitative approach. The sample was comprised of 14 children between the ages of three and twenty-four months with congenital cardiopathies. For the growth assessment, the Z score of weight-for-age and height-for-age were determined. For the developmental assessment, the Denver II was used. Results: the children presented a height and weight deficit of 42.85%, evidence by the Z score of weight-for-age and height-for-age less than or equal to -2. The congenital cardiopathies that most affected growth were interventricular communication and tetralogy of Fallot. As for development of these children, the study detected a suspected developmental delay in the personal-social (14,29%), language (14,29%) and motor (64,29%) areas. Conclusions: the results point up the importance of monitoring the growth and development of children with congenital cardiopathies by healthcare professionals, with the aim of minimizing the effects of these pathologies on nutritional states, a risk factor for worsening the health of these children. Parents must be advised about the importance of meeting these children's needs and establishing measures to reduce the negative impacts of cardiopathies on their children's growth and development.